The contest - Korman, Gordon (New York : Scholastic, 2002)
Dominic, Chris, Perry, Tilt, Sammi, Bryn, and Cameron compete with each other to be selected as part of a team of teenage climbers with the goal of ascending Mount Everest.
P
"An Apple paperback."
750
P
Keywords: Mountaineers -- Fiction; Children's stories; Adventure fiction